THE EFFECTIVENESS OF INQUIRY BASED LEARNING FOR NATURAL SCIENCE LEARNING IN ELEMENTARY SCHOOL - Laksana, Dek Ngurah Laba (Universitas Pendidikan Ganesha, 2017)
This paper primarily emphasized on describing the use of inquiry in natural science learning at primary school. This study also exposed the validity of inquiry strategy in natural science learning to improve primary schools studentsâ comprehension. Further, this present study employed a library research sourced from reputable journal articles in relation to the issue. Assisted inquiry strategy with 5E model became the one investigated. The model covered five phases namely, engaging, exploring, explaining, elaborating, and evaluating. Empirically, the inquiry strategy in natural science learning had proven improving the quality of learning and the learning achievement, particularly in conceptual learning